2015
DOI: 10.1002/2015gl063570
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of large‐scale contractional tectonic landforms on Mercury: Implications for the origin of global stresses

Abstract: The surface of Mercury is dominated by contractional tectonic landforms that are evidence of global‐scale crustal deformation. Using MESSENGER orbital high‐incidence angle imaging and topographic data, large‐scale lobate thrust fault scarps have been mapped globally. The spatial distribution and areal density of the contractional landforms are not uniform; concentrations occur in longitudinal bands and between the north and south hemispheres. Their orientations are generally north‐south at low latitude to midl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 42 publications
5
38
0
Order By: Relevance
“…In contrast, within the ICP, h varies between 0.09 and 3 km, with a median of 0.57 km. This difference in relief is consistent with previous studies (Byrne et al, ; Watters et al, ; Melosh & McKinnon, ; Watters & Nimmo, ; Strom et al, ). In the SP, ~80% of structures have h less than 0.5 km, compared with only ~40% of structures in the ICP (Figure S1 in the supporting information).…”
Section: Characterizing Fault Morphologysupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, within the ICP, h varies between 0.09 and 3 km, with a median of 0.57 km. This difference in relief is consistent with previous studies (Byrne et al, ; Watters et al, ; Melosh & McKinnon, ; Watters & Nimmo, ; Strom et al, ). In the SP, ~80% of structures have h less than 0.5 km, compared with only ~40% of structures in the ICP (Figure S1 in the supporting information).…”
Section: Characterizing Fault Morphologysupporting
confidence: 92%
“…Shortening structures found in the SP are regarded as analogous to the wrinkle ridges in the lunar maria (Melosh, ) and may reflect, at least in part, loading‐induced stresses from the volcanic infill (Byrne et al, ; Melosh & McKinnon, ; Solomon & Head, ; Watters et al, ). Furthermore, the style of faulting in the SP may have been influenced by mechanical detachments within volcanic strata producing “thin‐skinned” faulting (i.e., faulting restricted mainly to the volcanic units), whereas ICP shortening structures may be “thick‐skinned” (i.e., deeper faulting that may even have penetrated to the contemporary brittle‐ductile transition) (Byrne et al, ; Watters et al, ; Watters et al, ). Together, these characteristics suggest that the total shortening strain, and in particular that due to global contraction, should be less in the SP than the ICP.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of planetary radius decrease estimated from the mapped population of faults in Byrne et al [] was found to range from 3.1 to 7.1 km, with the variance a function once more of assumed fault population statistics. The work presented in Watters et al [] possessed far fewer thrust fault‐related landforms than reported by Byrne et al [] and did not provide estimates of the amount of global contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer, but still essentially globally distributed scarp segments, are superposed by Mansurian and Calorian craters. A notable exception to the above statements regarding geographic distribution is that few lobate scarp segments are seen on Mercury's smooth plains (Figures and ), where wrinkle ridges are the dominant contractional landforms [e.g., Byrne et al , ; Watters et al , ].…”
Section: Discussionmentioning
confidence: 99%